Fish Catch Composition and Its’ Bearing on the Income of Fishers: A Case Study of Chandakhal Wetland, Dhubri, Assam, India - Sheikh S.; Goswami M. M. (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
Fishing is a traditional economic activity with tremendous socio-economic impact in the rural sector of India. In the state of Assam (India), the fishers are distinctive communities who are associated with the fish and fisheries of the region for their livelihood from time immemorial. The present study aims to know the fish catch composition of Chandakhal wetland of Dhubri district in the state of Assam, India and its’ bearing on the income of the fishers dependent on the wetland. The study is based on the data of fish catch composition (in Kilogram) and the fishers’ income (in Indian National Rupee) followed by its suitable statistical analysis using SPSS (Version 16.0). The findings bring about the result that 93.6% of the Fishers’ income’ is explained only by Catch of intermediate fish. At the same time the finding also shows that there is variation of 96.8% in the Fisher’s income being influenced by the variations in the catch of Intermediate and Minor fishes together. While there is 98.6% variation in the Fisher’s income being expressed by the variations in the Catch of Intermediate, Minor and Major fishes jointly. It is inferred from the present study that the income of Fisher of the study area is highly dependent on the catch of intermediate fish group followed by the minor fish group and major fish group.